Immigration and self-reported health status by social class and gender: the importance of material deprivation, work organisation and household labour. Issue 5 (15th April 2008) - Borrell, C; Muntaner, C; Solè, J; Artazcoz, L; Puigpinós, R; Benach, J; Noh, S
Abstract : Objective: Spain and Catalonia have experienced several immigration waves over the last century. The goal of this study was to examine the role of social class and its mediating pathways (ie, work organisation, material deprivation at home and household labour) in the association between migration status and health, as well as whether these associations were modified by social class or gender. Setting: Barcelona city, Spain. Design and participants: The study used the Barcelona Health Interview Survey, a cross-sectional survey of 10 000 residents of the city's non-institutionalised population in 2000. The present study was conducted on the working population, aged 16–64 years (2342 men and 1872 women). The dependent variable was self-reported health status. The main independent variable was migration status. Other variables were: social class (measured using Erik Olin Wright's indicators); age; psychosocial and physical working conditions; job insecurity; type of labour contract; number of hours worked per week; material deprivation at home and household labour. Two hierarchical logistic regression models were built by adding different independent variables. Results: Among men, foreigners presented the poorest health status (fully adjusted odds ratios (OR) 2.16; 95% CI 1.14 to 4.10), whereas among women the poorest health status corresponded to those born in other regions of Spain. There was an interaction between migration and social class among women, with women owners, managers, supervisors or professionals born in other regions of Spain reporting a worse health status than the remaining groups (fully adjusted OR 3.60; 95% CI 1.83 to 7.07). Conclusion: This study has shown that the pattern of perceived health status among immigrant populations varies according to gender and social class. These results have to be taken into account when developing policies addressed at the immigrant population.